The biphasic regulatory effect of adenosine A2B receptor in ischemic brain injury and its therapeutic potential - Xu Rui; Wang Xi; Li Mengzhu; Su Peiwei; Liu Mudong; Zhu Chao; Luo Wanyu; Zhao Haijun (Purinergic Signalling, 2026)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.